The diary : the epic of everyday life - Ben-Amos, Batsheva; Ben-Amos, Dan (Indiana University Press, 2020)
"The diary as a genre is found in all literate societies, and these autobiographical accounts are written by persons of all ranks and positions. The Diary offers an exploration of the form in its social, historical, and cultural-literary contexts with its own distinctive features, poetics, and rhetoric. The contributors to this volume examine theories and interpretations relating to writing and studying diaries; the formation of diary canons in the United Kingdom, France, United States, and Brazil; and the ways in which handwritten diaries are transformed through processes of publication and digitization. The authors also explore different diary formats, including the travel diary, the private diary, conflict diaries written during periods of crisis, and the diaries of the digital era, such as blogs. The Diary offers a comprehensive overview of the genre, synthesizing decades of interdisciplinary study to enrich our understanding of, research about, and engagement with the diary as literary form and historical documentation"--